A guide to research in music education - Ferrara, Lawrence; Phelps, Roger P.; Sadoff, Ronald F.; Warburton, Edward C. (Lanham Scarecrow Press, 2005)
This Fifth Edition presents an updated and practical approach to the research concepts, techniques, and sources from the 4th edition. A new chapter concerning music and technology covers the current available resources for students and researchers. Other updates include separate chapters on philosophical inquiry and aesthetic inquiry becoming integrated, formulating and implementing research problems, and aligning qualitative research with recent concepts and techniques.This is an essential tool for students tackling problems as varied as research proposals, field research strategies, data analysis, and statistical techniques. Researchers will find current sources and concise instruction in the formulation of a research proposal, its implementation, and dissemination of research results.